Registration of 'Focus' Hard Red Spring Wheat. Issue 1 (4th October 2018) - Glover, K. D.; Kleinjan, J. L.; Jin, Y.; Osborne, L. E.; Ingemansen, J. A.; Turnipseed, E. B.; Dykes, L.
Abstract : Grower and end‐user acceptance of new hard red spring wheat (HRSW; Triticum aestivum L.) cultivars is heavily influenced by agronomic performance, end‐use quality potential, and disease resistance. The objective of this research was to release a new HRSW cultivar with competitive agronomic performance, end‐use quality, and disease resistance to serve as a replacement for 'Brick', a HRSW cultivar that has been very popular in South Dakota. 'Focus' (Reg. No. CV‐1148; PI 675337) HRSW was developed at South Dakota State University and released by the South Dakota Agricultural Experiment Station in early 2015. The cross SD3943‐21/'Brick' was completed during fall 2007, and the resulting population was advanced via an early‐generation bulk‐testing program, where F4:6 seed from the 2010 growing season was included in the 2011 preliminary yield trial, and the line was designated as SD4362. This line was also was tested in the advanced yield trial from 2012 through 2014. Focus was released primarily for its yield potential, high grain volume weight, early maturity, and good level of resistance to Fusarium head blight.